Implementation of Wafers Feed on Based Palm Kernel Cake for Adult Ongole Crossbreed Cattle - Sukaryana, Yana; Zairiful; Priabudiman, Yadi; Panjaitan, Imelda (Proceeding International Conference on Science and Engineering, 2020)
Wafer is one of the complete feed form processed feed which is formed in such a way with special tools, made from concentrate and forage. The purpose of this research was to implementation of wafer feed on based palm kernel cake for adult ongole crossbreed cattle. The cattle used was ongole crossbreed cattle, cow males used as much as 12 tails with approximately 2 years of age and average body weight 200 ± 25 kg. Wafer feed of based palm kernel cake treatment in 4 formulas, namely: Formula 1, Formula 2, Formula 3, and Formula 4. Feed was given ad libitum controlled and drinking water was given ad libitum. The observation variables were done against: feed consumption, weight gain, and feed conversion. The results showed that: Wafer feed of based palm kernel cake treatment has no significant (P > 0.05) influence against feed consumption in adult ongole crossbreed cattle, daily weight increase in mature ongole crossbreed cattle with wafer feed; Formula 1 of 0.63 kg/tail/day, Formula 2 is 0.60 kg/tail/day, Formula 3 is 0.73 kg/tail/day, and Formula 4 is 0.80 kg/tail/day, the best feed conversion in the range of feed Formula 4 ie (4.13), feed Formula 3 ie (4.53), feed Formula 1 ie (5.13), and feed Formula 2 ie (5.43).